Le fonds Jean Lattes : une archive photographique en construction - Angelina Meslem; Wilfrid Eon; Clémentine Vialar (In Situ)
The donation in 2011, by his widow Janine Lattes, of more than 180,000 photos taken by the photojournalist Jean Lattes (1917 - 1996) to the archive service of the Yvelines department forced its archivists to reflect on their practice. In addition to immediate preservation concerns such as the physical state of the documents, reconditioning and digitising, other questions relating to the intellectual treatment of this complex photographic collection have also arisen. Besides photos, the collection also comprises archives relating to Jean Lattes’s status as a freelance photographer, inventory books and a thematic catalogue. The transfer of the collection was a hasty affair, poorly documented at the time, and this affected the understanding of how the different documents relate to each other and of the codes that applied to the initial organisation, elaborated by the Lattes couple for the proper management of the collection. For this reason, understanding the context in which the photographs were produced seemed to be a preliminary necessity in order to conceive efficient research tools, to preserve the producer’s own references and annotations and to allow a cross-cutting approach to the various media conserved, negatives, contact sheets and publications. For this the reportage was the most pertinent intellectual unit.